Neagoe Basarab – modelul „omului desăvârșit și întreg” - Eugen Simion (Revista de Istorie și Teorie Literară)
This article is about the teachings of Neagoe Basarab in regards to the behavior of the future ruler. They are presented as a manual for practical morals where the orthodox faith intertwines with the bravery, merging the attributes of the Saint with those of the Hero. The religious significances of this moral code can be found under double appearance, for both division of the virtues (“Indwelling of God”, fasting, patience, love, gentleness, humility) and meeting of sins (lack of moderation in regards to gastronomy, drinking, gossiping, laughter and women, believed to be behind the many sins). Besides the theological instruction, the teachings of Neagoe Basarab puts into the foreground a moralist who knows the pitfalls and subtleties of the language, the finesse of meditation and the skill to push ideas to metaphysics. After Acad. Eugen Simion had commented the discursive levels of the chapters devoted to medieval diplomacy and art of the adorned speech (the parables and biblical parables), in the third part of this study the author focuses on the general meanings of the Teachings … Along with other specialists (Dan Zamfirescu, G. Mihăilă), the author believes that the paternity of the work belongs to Neagoe Basarab – even if specialists’ talks remain open – and this work, written in a liturgical language and translated into Romanian after a century, it has to be added to Romanian literary heritage. This real treatise – with teachings addressed to those who aspire to become fulfilled and upright people – does not avoid any of the great virtues of the ruler (in which Neagoe Basarab embodies the heroism and sanctity vocations) and it is our first masterpiece.